A comparison of sociodramatic play processes of preschoolers in a naturalized and a traditional outdoor space. Issue 2 (4th May 2017) - Morrissey, Anne-Marie; Scott, Caroline; Rahimi, Mark
ABSTRACT: Sociodramatic play processes such as role play, transformations, persistence, and metacommunication are regarded as both important markers and facilitators of development. They are also influenced by the nature of the environment and resources available. With increased interest in the influence of naturalized play environments on sociodramatic play, researchers in this study used event sampling to compare sociodramatic play processes of 4- to 5-year-olds in two spaces at their preschool: one traditional and one highly naturalized. Play episodes in the naturalized space persisted for longer, were more mobile, and involved more fantasy role play. A chi-square analysis showed that children in the naturalized yard also demonstrated significantly higher levels of object substitutions, imaginative transformations, and metacommunications. Greater affordance of open-ended materials, flexible playscapes, and a greater sense of seclusion and quiet are proposed as possible factors, with implications for practice and design.